Responses of Escherichia coli and Listeria monocytogenes to ozone treatment on non-host tomato: Efficacy of intervention and evidence of induced acclimation - Xiaomei Shu; Manavi Singh; Naga Bhushana Rao Karampudi; David F. Bridges; Ai Kitazumi; Vivian C. H. Wu; Benildo G. De los Reyes (PLoS ONE, 2021)
Because of the continuous rise of foodborne illnesses caused by the consumption of raw fruits and vegetables, effective post-harvest anti-microbial strategies are necessary. The aim of this study was to evaluate the anti-microbial efficacy of ozone (O3) against two common causes of fresh produce contamination, the Gram-negative Escherichia coli O157:H7 and Gram-positive Listeria monocytogenes, and to relate its effects to potential mechanisms of xenobiosis by transcriptional network modeling. The study on non-host tomato environment correlated the dose × time aspects of xenobiosis by examining the correlation between bacterial survival in terms of log-reduction and defense responses at the level of gene expression. In E. coli, low (1 μg O3/g of fruit) and moderate (2 μg O3/g of fruit) doses caused insignificant reduction in survival, while high dose (3 μg/g of fruit) caused significant reduction in survival in a time-dependent manner. In L. monocytogenes, moderate dose caused significant reduction even with short-duration exposure. Distinct responses to O3 xenobiosis between E. coli and L. monocytogenes are likely related to differences in membrane and cytoplasmic structure and components. Transcriptome profiling by RNA-Seq showed that primary defenses in E. coli were attenuated after exposure to a low dose, while the responses at moderate dose were characterized by massive upregulation of pathogenesis and stress-related genes, which implied the activation of defense responses. More genes were downregulated during the first hour at high dose, with a large number of such genes getting significantly upregulated after 2 hr and 3 hr. This trend suggests that prolonged exposure led to potential adaptation. In contrast, massive downregulation of genes was observed in L. monocytogenes regardless of dose and exposure duration, implying a mechanism of defense distinct from that of E. coli. The nature of bacterial responses revealed by this study should guide the selection of xenobiotic agents for eliminating bacterial contamination on fresh produce without overlooking the potential risks of adaptation.